Respostas

2014-06-06T20:27:49-03:00
Veja: 
I = ∫ x³ cos x dx 
u=x³ 
dv=cos x dx 
du=3x²dx 
v=senx 

∫ udv=uv - ∫ vdu 

∫ x³ cos (x) dx= 
x³.sen(x) - 3∫ x²sen(x)dx 

∫ x²sen(x)dx= 
II = ∫ x² sen (x) dx 
u=x² 
dv=sen(x) dx 
du=2xdx 
v=-cos(x) 

II = ∫ x² sen (x) dx= 
x²cos(x) + ∫ 2x cos (x) dx 

III=∫ x cos (x) dx= 
u=x 
dv=cos x dx 
du=dx 
v=senx 

∫ x cos (x) dx= 
x.sen(x) - ∫ sen(x)dx= 
x.sen(x) + cos(x) + c 

Voltando em II,temos: 
x²cos(x) + ∫ 2x cos (x) dx= 
x²cos(x) + 2∫ x cos (x) dx= 
x²cos(x) + 2.[x.sen(x) + cos(x)] + c 

Espero ter ajudado 
A tá , entendi , vou tentar fazer dessa outra forma ,
Por nada
a resposta é:
Sim
1/5 [ ln |2tg(x/2)-1|- ln |tg(x/2)+2|] +c